STRONTIUM ABUNDANCES IN COOL DWARF STARS OF GALACTIC THIN AND THICK DISKS - Gorbaneva, T. I.; Mishenina, T. V. (Одеські астрономічні публікації, 2016)
We revise the strontium abundances in FGK stars with metallicities ranging from −1.0 < [Fe/H] < +0.3. The observed stars belong to the substructures of the Galaxy thick and thin discs. The observations were conducted using the1.93 mtelescope at Observatoire de Haute-Provence (OHP, France) equipped with the echelle type spectrographs ELODIE and SOPHIE. The values of the Sr abundance were obtained using synthetic spectra using LTE model atmosphere. The comparison of our data with models of chemical evolution was made.